2013
DOI: 10.1074/jbc.m112.400184
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Regulates MyoD Expression and Activity

Abstract: Background: Hedgehog (Hh) signaling regulates skeletal myogenesis; however, the molecular mechanisms involved are not fully understood.Results: Gli2, a transactivator of Hh signaling, associates with MyoD gene elements, regulating MyoD expression, and binds to MyoD protein, regulating its ability to induce myogenesis.Conclusion: Hh signaling is linked to MyoD gene expression and MyoD protein function.Significance: Novel mechanistic insight is gained into the Hh-regulated myogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 111 publications
(191 reference statements)
5
35
0
1
Order By: Relevance
“…This is similar to several studies in mice, in which Gli2 appears to be the primary transcriptional activator, while Gli1 is not required for embryonic development (Mo et al , 1997; Ding et al , 1998; Bai et al , 2002). Indeed, in P19 cells, Gli2 is upregulated rather than Gli1 after 5 days of cell differentiation (Voronova et al , 2013), which is similar to what is seen in our study. Moreover, reports have shown that Gli2 regulates Pax3 and MyoD expression during skeletal and cardiac myogenesis (Petropoulos et al , 2004; Voronova et al , 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to several studies in mice, in which Gli2 appears to be the primary transcriptional activator, while Gli1 is not required for embryonic development (Mo et al , 1997; Ding et al , 1998; Bai et al , 2002). Indeed, in P19 cells, Gli2 is upregulated rather than Gli1 after 5 days of cell differentiation (Voronova et al , 2013), which is similar to what is seen in our study. Moreover, reports have shown that Gli2 regulates Pax3 and MyoD expression during skeletal and cardiac myogenesis (Petropoulos et al , 2004; Voronova et al , 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that Shh signaling is essential for myogenesis in zebrafish since without Shh signaling, adaxial cells are delayed in terminal differentiation (Coutelle et al , 2001). In mouse cells, hedgehog signaling regulates both cardiac and skeletal myogenesis, as the transcription factor of hedgehog signaling, Gli2, has been shown to regulate and activate Mef2c and MyoD expression, which are transcription factors needed for myogenic differentiation of progenitor cells (Voronova et al , 2012; Voronova et al , 2013). Shh signaling is also critical for neuronal development.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Gli1 was elevated on the 3rd and 9th days, but its expression declined on the 6th day. A similar expression profile of Gli1 and Gli2 was observed in dimethyl sulfoxide-induced P19 cells (Voronova et al, 2013).…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, the repression of the Hh signaling pathway induced by cyclopamine or a small interfering RNA (siRNA) of its positive component inhibited chondrogenic differentiation (Wu et al, 2013). The Hh signaling pathway promotes myogenesis in zebrafish (Flynt et al, 2007;Lobbardi et al, 2011), Xenopus (Martin et al, 2007), mouse (Straface et al, 2009;Hu et al, 2012;Voronova et al, 2013), and chick (Elia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among the Glis, Gli1 is the principal transcription factor in the Shh pathway, and many studies have shown that it is of great importance in skeletal muscle regeneration [20, 27, 28]. Furthermore, Gli2 activity has been confirmed to be sufficient and required for efficient MyoD treatment during skeletal myogenesis [29], which plays a major role in regulating muscle differentiation during embryogenesis and adult muscle regeneration [30]. Based on these data, we speculate that both Gli1 and Gli2 are crucial for the process by which Shh modulates skeletal muscle I/R injury.…”
Section: Discussionmentioning
confidence: 99%